ANALISIS PERAN SYEKH ABDUL RAUF SINGKEL TERHADAP PENDIDIKAN TASAWUF DAN FIQIH DI UJUNG SUMATRA - Niswah, Choirun; Ghifari, Muhammad Rafi Al; Puspa, Hayatul; Azizah, Dina Nur (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
Aceh, as the intellectual center of Islam in the Indonesian archipelago, produced the great scholar Sheikh Abdul Rauf Singkel, who played a vital role in the transmission of Islamic knowledge. This study aims to analyze Sheikh Abdul Rauf Singkel's strategic contribution to the development of Sufism and Islamic jurisprudence education in the Indonesian archipelago. Using a qualitative approach and library research, this study examines his monumental works, such as Mir'at al-Thullab and Turjuman al-Mustafid, in depth, as well as related historical literature. The main findings indicate that Sheikh Abdul Rauf successfully harmonized the legal-oriented Islamic jurisprudence discipline with Sufism, which emphasizes spirituality, creating a moderate and balanced model of Islamic education. As the authority of Qadi Malik al-Adil and the propagator of the Syatariyah Order, he was not only prolific in writing books but also successfully established a network of scholars connecting the Haramain with the Indonesian archipelago, as evidenced by the spread of his students to various regions such as Minangkabau and Java. It is concluded that the integration of knowledge he initiated became an important foundation for the Islamic education system in Southeast Asia, emphasizing the balance between sharia and reality, as well as the formation of solid moral character within Malay civilization. ABSTRAKAceh, sebagai pusat intelektual Islam di Nusantara, melahirkan ulama besar Syekh Abdul Rauf Singkel yang memegang peranan vital dalam transmisi keilmuan Islam. Penelitian ini bertujuan menganalisis kontribusi strategis Syekh Abdul Rauf Singkel terhadap pengembangan pendidikan tasawuf dan fiqih di Ujung Sumatra. Melalui pendekatan kualitatif dengan metode studi pustaka (library research), penelitian ini menelaah secara mendalam karya-karya monumental beliau, seperti Mir’at al-Thullab dan Turjuman al-Mustafid, serta literatur sejarah terkait. Temuan utama menunjukkan bahwa Syekh Abdul Rauf berhasil melakukan harmonisasi antara disiplin fiqih yang berorientasi hukum dengan tasawuf yang menekankan spiritualitas, menciptakan model pendidikan Islam yang moderat dan seimbang. Sebagai pemegang otoritas Qadi Malik al-Adil dan penyebar Tarekat Syatariyah, beliau tidak hanya produktif dalam penulisan kitab, tetapi juga sukses membangun jejaring ulama yang menghubungkan Haramain dengan Nusantara, terbukti dari penyebaran murid-muridnya ke berbagai wilayah seperti Minangkabau dan Jawa. Disimpulkan bahwa integrasi keilmuan yang digagasnya menjadi fondasi penting bagi sistem pendidikan Islam di Asia Tenggara yang menekankan keseimbangan antara syariat dan hakikat, serta pembentukan karakter akhlak yang kokoh dalam peradaban Melayu.